Method for filling through holes to reduce voids
Patent Information
- Application Number
- JP2023027446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-04
- Filing Date
- 2023-02-24
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-02-24
Smart Images

Figure 0007634584000005 
Figure 0007634584000006 
Figure 0007634584000007
Abstract
Description
[Technical field]
[0001] The present invention is directed to a method of filling through holes to reduce voids with phase shift pulse plating, more specifically, the present invention is directed to a method of filling through holes to reduce voids with phase shift pulse plating by forming a partial bridge in the through hole followed by pulse plating reversal to completely fill the through hole. [Background technology]
[0002] Filling through holes with copper plating is becoming more difficult as through holes get higher aspect ratio. This can result in larger voids and other defects. Another issue with through hole filling is the method of filling the through holes. Unlike vias, which are closed at one end, through holes penetrate the board and are open at two ends. Vias are filled from bottom to top. In contrast, through holes are filled by forming a complete copper bridge (forming a "butterfly") in the center of the through hole, as shown in Figure 4, and then filling the two vias formed on either side of the copper through hole bridge. Direct current (DC) plating is performed at 1.5 or 2 amps / dm2 for a 200 μm thick, 100 μm diameter through hole (aspect ratio = 2). 2 The through holes can be filled with constant current plating (ASD). Figure 5 shows a conventional DC waveform. As the aspect ratio increases, it becomes more difficult to fill the through holes, and DC plating only results in conformal filling. For example, a 900 μm thick, 250 μm diameter through hole (aspect ratio=3.6) is more difficult to fill than a 900 μm thick, 150 μm diameter through hole (aspect ratio=6.0) with an aspect ratio of 2. In many cases, the copper cannot completely fill the through hole, leaving both ends unfilled, and voids of various sizes can form within the copper through hole fill.
[0003] Conventional pulse plating reversal (PPR) processes also fail to fill high aspect ratio through holes. Phase shift PPR techniques have been used to first form a complete copper bridge in the center of the through hole to form two vias, and then fill the vias by DC plating. Phase shift pulse plating is a technique in which the same pulse waveform is applied to each side of the board (controlled by separate rectifiers) and the waveform is offset to a specific angle (e.g., 0°, 90°, 180°). Phase shift refers to the difference in the start time of the pulse, expressed as an angle that is a percentage of a full cycle of 360°. However, such phase shift PPR plating processes are not always reliable and often result in incomplete filling of the through hole, with significant formation of undesirable voids in the copper fill.
[0004] An ideal process would completely fill the through-holes with a high degree of planarity, i.e., build-up consistency, without voids, and at a low surface thickness for optimal linewidth and impedance control in electrical devices to provide optimal reliability and electrical properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] U.S. Pat. No. 8,268,158 Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, a need exists for a method to improve the filling of high aspect ratio through holes in substrates such as printed circuit boards. [Means for solving the problem]
[0007] 1. A method comprising: a) providing a substrate including a first side and a second side having a plurality of through holes; b) immersing the substrate in a copper plating bath; c) simultaneously polarizing the first side of the substrate with a rectifier and polarizing the second side of the substrate with a rectifier to generate currents on the first side and the second side of the substrate; d) plating partial copper bridges in the through holes by simultaneously applying a plating cycle to the first and second sides of the substrate, the plating cycle including applying a DC current on the first and second sides of the substrate, followed by applying a first pulse train on the first side of the substrate and a second pulse train on the second side of the substrate, the first pulse train and the second pulse train being offset by 180°; and then e) filling the through-holes with copper by applying a pulsed plating reverse current to the board; The method includes:
[0008] Previously, it was believed necessary to completely bridge the through holes before switching to the next step of through-hole filling, however, the method of the present invention may allow for defect-free filling at lower surface copper by partially bridging the through holes and then completely filling them by using pulse plating reversal. [Brief description of the drawings]
[0009] [Figure 1A] 1 shows phase shifted waveforms of current density versus time (in seconds) offset by 180° on the A and B sides of a board with multiple through holes. [Figure 1B] 1 shows a pulse plating inverse waveform of current density versus time for completely filling a through-hole with a partial copper bridge. [Diagram 2] 1 shows a cross section of a through hole of a partial copper bridge. [Diagram 3] 1 shows a cross section of a through hole of a partial copper bridge specifying variables X and Y for determining parameters of the partial copper bridge. [Figure 4] 1 shows a cross section of a full copper bridge through hole. [Diagram 5] 1 shows a DC waveform of current density versus time in seconds for filling a through-hole with a full copper bridge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] As used throughout this specification, the abbreviations set forth below have the following meanings, unless the context clearly dictates otherwise: g = grams; mL = milliliters; L = liters; cm = centimeters; μm = microns; ppm = parts per million = mg / L; ppb = parts per billion; °C = degrees Celsius; g / L = grams per liter; DC = direct current; PPR = pulse plating reversal; ASD = amperes / dm 2 ;AR = aspect ratio; 2D = two-dimensional; DI = deionization; sec = seconds; ms = milliseconds; wt% = weight percent; and void = copper-free space within a through-hole that is filled with copper metal.
[0011] The terms "printed circuit board" and "printed wiring board" are used interchangeably throughout this specification. The term "substrate" includes, but is not limited to, electroless plated or SHADOW metallized printed circuit boards and electroless plated metallized glass. The term "SHADOW" refers to a conductive graphite surface. The terms "plating" and "electroplating" are used interchangeably throughout this specification. The terms "composition" and "bath" are used interchangeably throughout this specification. The term "pulse train" refers to a series of forward (cathode)-reverse (anodic) current pulses of a given current density and for a given duration. The term "phase shift" refers to the difference in the start time of the applied waveform, expressed as an angle that is a fraction of a full cycle of 360°. The term aspect ratio refers to the through-hole thickness / through-hole diameter. The term "cycle" refers to a series of events that are repeated in the same order. The term "DC current" refers to unidirectional flow of current. The term "pulse plating reversal" refers to an electroplating process in which the current alternates between a cathode current (forward pulse) and an anodic current (reverse pulse) during the electroplating process. The term "void" within the scope of the present invention means a space or pocket that is substantially free of copper deposit, but is within the copper deposit. The term "pitch" means the frequency of through-hole locations from one another on a board. The term "conformal plating" means copper plating (deposition) to the contours of the board surface. The term "immediately" means that there is no intervening step. All amounts are weight percent unless otherwise noted. All numerical ranges are inclusive of both ends and can be combined in any order, except where it is logical to constrain such numerical ranges to add up to 100%.
[0012] Phase-shift electroplating is performed simultaneously on the first or A side of the substrate and the second or B side of the substrate during the formation of a partial bridge in the through-hole of the substrate. Electroplating on each side of the substrate includes (and preferably consists of) DC electroplating, which deposits copper on the surface of the substrate and on the walls of the through-hole, followed by a pulse train to strip the copper from the surface of the substrate and the walls of the through-hole. Cycles of DC plating followed by a pulse train are repeated simultaneously on both sides of the substrate until a partial bridge is formed in the through-hole. FIG. 2 is an example of a cross-section of a through-hole 10 having a partial bridge 20. The surface of the substrate 12 is plated with copper 14 and the walls 16 of the through-hole 10 are plated with copper 18 such that the partial bridge 20 is formed substantially in the center of the through-hole 10 leaving a gap 22 between each half of the partial bridge. The through-hole 10 has openings 24A and 24B at both ends.
[0013] At least one pulse train on the first or A side of the substrate is offset by a phase shift of 180° with respect to at least one pulse train on the second or B side of the substrate. The waveform is such that DC plating predominates on both sides of the substrate during the method. The first side (A) or the second side (B) of the substrate can start with DC plating. While DC plating is performed on one side of the substrate, a forward (cathode)-reverse (anode) current pulse train (copper stripping) is simultaneously applied on the other side of the substrate. After a certain time, the DC plated side of the substrate is changed to a forward (cathode)-reverse (anode) current pulse train (copper stripping) and DC plating is performed on the opposite side to the previous pulse train. For example, when DC plating is started on the second side (B), a pulse train is simultaneously also applied to the first side (A). After a predetermined time, DC plating continues on the first side (A) while a pulse train of forward (cathode)-reverse (anodic) current (copper stripping) is applied to the second side (B) of the board. The pulse train on the first side of the board and the pulse train on the second side of the board occur at predetermined time intervals through a phase-shifted cycle, which cycle covers 360°. Figure 1A is an example of one cycle of DC current followed by a pulse train of forward-reverse current with a phase shift of 180°, simultaneously electroplating on both sides of a board having multiple through-holes.
[0014] Conventional electroplating equipment can be used for plating the through-holes. An apparatus that can be used to electroplate a substrate containing a plurality of through-holes includes a rectifier to provide a voltage drop on each side (cathode) of the substrate. The rectifier is electrically connected to a counter electrode or anode. The substrate and counter electrode are immersed in a vessel containing a copper electroplating bath or composition.
[0015] During the phase shift cycle, preferably the DC current density is in the range of 0.5 to 10 ASD, more preferably 1 to 5 ASD, and most preferably 1 to 3 ASD. Preferably, during the phase shift cycle, the DC current is applied for 1 to 60 seconds, more preferably 1 to 40 seconds, and most preferably 1 to 20 seconds.
[0016] During the phase shift cycle, preferably, the pulse train of forward - reverse current has a forward current density of 0.5 to 10 ASD, more preferably 1 to 5 ASD, and most preferably 1 to 3 ASD, and preferably has a reverse current density of - 1.5 to - 30 ASD, more preferably - 3 to - 15 ASD, and most preferably - 3 to - 9 ASD. Preferably, the forward current to reverse current ratio is 1:3. The times of the forward pulses and reverse pulses of the pulse train can be the same or different. Preferably, the times of the forward pulses and reverse pulses are of the same duration. Preferably, the forward pulses and reverse pulses have a duration of 25 to 1000 milliseconds, more preferably 50 to 500 milliseconds, and most preferably 50 to 200 milliseconds. The pulse train is illustrated within the dashed rectangle of FIG. 1A.
[0017] The phase shift cycle is repeated until a desired partial bridge is formed in substantially all of the through - holes of the substrate. If the duration of the phase shift plating is too long, the surface roughness increases, leading to void formation at the bridge points, and voids begin to form within the through - holes.
[0018] Ultra - conformal growth of copper deposits inside the through - holes is the case where the maximum thickness of the plating deposits inside the through - holes is greater than the thickness of the deposits on the surface around the through - holes. The partial bridges within the scope of the present invention are ultra - conformal growths having a ratio in microns (μm) at the thickest point of the copper in the through - holes: greater than 0 but less than 1, of the ratio of the diameter of the through - hole in microns (μm). Preferably, this ratio ranges from greater than 0.25 and less than 0.9. By definition, a value of 0 indicates no plating within the through - hole. The copper plating on the walls of the through - holes can be either conformal or ultra - conformal. A value of 1 indicates complete bridge formation such that two vias are formed within the through - hole. This ratio can be represented by the following two equations with respect to the cross - section of the through - hole. 0 < X + Y / D < 1 (I), or 0 < (X + Y) / 2 / D / 2 < 1 (II) where X is the thickest point in the first half of the through-hole, Y is the thickest point in the second half of the through-hole opposite X, and D is the diameter of the through-hole before plating.
[0019] 3 shows a cross section of a through hole 30 in a substrate 32 that has been plated with a copper layer 34 and a partial copper bridge 36, half X and half Y, and of diameter D. The partial copper bridge 36 forms a figure eight configuration in the through hole 30 with a gap 38 between the two thickest points in the through hole. The through hole 30 has two open ends 40.
[0020] In contrast, Figure 4 shows a through hole 50 in a substrate 52 plated with a copper layer 54 and a full copper bridge 56 forming two vias 58 and 60, where the ratio is one.
[0021] The means of measuring the through-hole parameters to determine this ratio are not limited. For example, the through-hole can be cross-sectioned and the two halves of the through-hole measured at their thickest points. Preferably, the parameters are measured by X-ray analysis, such as with a Nordson Dage QUADRA™ 5 X-ray inspection system. X-ray analysis allows for 2D analysis of the through-hole.
[0022] After partial bridging of the through-holes is substantially complete, the copper filling of the through-holes is completed by pulse plating reversal (PPR). In the PPR stage of filling the through-holes of the present invention, a forward pulse current is applied followed by a reverse pulse current. No DC current is applied during the PPR stage of filling the through-holes of the present invention. FIG. 1B shows a PPR cycle in which a forward pulse current is followed by a reverse pulse current, then a second forward current, then a second reverse current. The PPR cycle can be repeated until the through-holes are filled with copper.
[0023] The forward pulse current is in the range of 0.5 to 10 ASD, more preferably 1 to 5 ASD, and most preferably 1 to 3 ASD. Preferably, the forward current is applied for 10 to 100 ms, more preferably 10 to 80 ms, and most preferably 15 to 50 ms. Preferably, the reverse or anodic current is in the range of -0.15 to -2.5 ASD, more preferably -0.25 to -1.25 ASD, and most preferably -0.25 to -0.75 ASD. Preferably, the ratio of forward current to reverse current is 1:0.25. Preferably, the reverse current is applied for 1 to 10 ms, more preferably 1 to 5 ms, and most preferably 1 to 3 ms.
[0024] Preferably, the substrate is a printed circuit board or wiring board having an average thickness of 150 to 800 μm, more preferably 250 to 800 μm, and most preferably 250 to 400 μm. Preferably, the through-holes have an average diameter of 100 to 300 μm, more preferably 100 to 250 μm, and most preferably 200 to 250 μm.
[0025] A printed circuit board with a thickness of 250 μm, an average through-hole diameter of 100 μm, and a plated surface copper thickness of 3 to 9 μm has a ratio of copper in the through-hole at its thickest point:diameter of the through-hole of 0.28 to 0.80. A board with a thickness of 250 μm, an average through-hole diameter of 150 μm, and a plated surface copper thickness of 7 to 9 μm has a ratio of 0.48 to 0.80. A board with a thickness of 400 μm, an average through-hole diameter of 200 μm, and a plated surface copper thickness of 10 μm to 13 μm has a ratio of 0.48 to 0.70. A board with a thickness of 800 μm, an average through-hole diameter of 250 μm, and a plated surface copper thickness of 10 to 14 μm has a ratio of 0.69 to 0.85.
[0026] Preferably, the AR is from 1.6:1 to 5:1, more preferably from 1.2:1 to 2.6:1, and most preferably, the AR is from 1.6:1 to 2:1.
[0027] The pitch of the through holes is preferably 200 to 1000 μm, more preferably 300 to 1000 μm, and most preferably 500 to 1000 μm.
[0028] The copper layer thickness and the presence of voids in the through-holes can be measured using conventional methods. An example of a conventional method for measuring the copper layer thickness and the presence of voids is X-ray analysis.
[0029] Preferably, the copper electroplating bath is agitated during the electroplating process to fill the through-holes to encourage the copper bath additives to be uniformly deposited over the surface of the substrate and within the through-holes. Any conventional plating bath agitation equipment can be used. Preferably, the bath agitation is from 4 L / min to 24 L / min, more preferably from 4 L / min to 16 L / min. Preferably, the plating temperature is in the range of 15-30°C, more preferably from room temperature to 30°C.
[0030] Prior to filling the through-holes, it is preferred to plate the substrate with an electroless copper layer such that the electroless copper is adjacent to the surface of the substrate and the walls of the through-holes. Conventional electroless copper plating baths and conventional electroless plating methods can be used to deposit the copper layer. Such electroless copper baths and methods are well known in the art and literature. An example of a commercially available electroless copper bath is CIRCUPOSIT™ 253 Electroless Process Plating Formulation and Method (available from DuPont Electronics & Industrial, Marlborough, MA). Preferably, the electroless copper has a thickness of 0.25 μm to 6 μm, more preferably 0.25 μm to 3 μm.
[0031] The substrate preferably comprises thermosets, thermoplastics and combinations thereof including fibers such as fiberglass, and the impregnated embodiments described above.
[0032] Thermoplastic resins include, but are not limited to, acetal resins, acrylic resins such as methyl acrylate, cellulosic resins such as ethyl acetate, cellulose propionate, cellulose acetate butyrate and nitrocellulose, polyethers, nylons, polyethylene, polystyrene, styrene blends such as acrylonitrile-styrene copolymers and acrylonitrile-butadiene-styrene copolymers, polycarbonates, polychlorotrifluoroethylene, and vinyl polymers and copolymers such as vinyl acetate, vinyl alcohol, vinyl butyral, vinyl chloride, vinyl chloride-acetate copolymer, vinylidene chloride, and vinyl formal.
[0033] Thermosetting resins include, but are not limited to, allyl phthalate, furan, melamine-formaldehyde, phenol-formaldehyde and phenol-furfural copolymers, alone or blended with butadiene acrylonitrile copolymers or acrylonitrile-butadiene-styrene copolymers, polyacrylic esters, silicones, urea formaldehyde, epoxy resins, allyl resins, glyceryl phthalate and polyesters.
[0034] Conventional acid copper electroplating baths can be used to seal and fill the through-holes. In addition to a source of copper ions, the copper electroplating baths preferably contain one or more brighteners, levelers, and suppressors. Conventional brighteners, levelers, and suppressors can be used.
[0035] Sources of copper ions include, but are not limited to, water-soluble halides, nitrates, acetates, sulfates, and other organic and inorganic salts of copper. Mixtures of one or more of such copper salts can be used to provide the copper ions. Examples include copper sulfate, such as copper sulfate pentahydrate, copper chloride, copper nitrate, copper hydroxide, and copper sulfamate. Conventional amounts of copper salts can be used in the composition. Copper salts are included in the bath in amounts of 50 g / L to 350 g / L, typically 100 g / L to 250 g / L.
[0036] The acids include, but are not limited to, sulfuric acid, hydrochloric acid, hydrofluoric acid, phosphoric acid, nitric acid, sulfamic acid, and alkylsulfonic acids. Such acids are included in conventional amounts. Preferably, such acids are included in the acid copper bath in an amount of 25 g / L to 350 g / L.
[0037] Examples of the brightening agents include 3-mercapto-propylsulfonic acid and its sodium salt, 2-mercapto-ethanesulfonic acid and its sodium salt, bissulfopropyl disulfide and its sodium salt, 3-(benzothiazolyl-2-thio)-propylsulfonic acid sodium salt, 3-mercaptopropane-1-sulfonic acid sodium salt, ethylenedithiodipropylsulfonic acid sodium salt, bis-(p-sulfophenyl)-disulfide disodium salt, bis-(ω-sulfobutyl)-disulfide disodium salt, bis-(ω-sulfohydroxypropyl)-disulfide disodium salt, bis-(ω-sulfopropyl)-disulfide disodium salt, bis-(ω-sulfopropyl)-sulfide disodium salt, methyl-(ω-sulfopropyl)-dis ... Examples of suitable brighteners include, but are not limited to, methyl-(ω-sulfopropyl)-disulfide sodium salt, methyl-(ω-sulfopropyl)-trisulfide disodium salt, O-ethyl-dithiocarbonic acid-S-(ω-sulfopropyl)-ester, potassium salt thioglycolic acid, thiophosphoric acid-O-ethyl-bis-(ω-sulfopropyl)-ester disodium salt, thiophosphoric acid-tris(ω-sulfopropyl)-ester trisodium salt, N,N-dimethyldithiocarbamic acid (3-sulfopropyl) ester, sodium salt, (O-ethyldithiocarbonato)-S-(3-sulfopropyl)-ester, potassium salt, 3-[(amino-iminomethyl)-thio]-1-propanesulfonic acid and 3-(2-benzothiazolylthio)-1-propanesulfonic acid, sodium salt. Preferably, the brightener is bissulfopropyl disulfide or its sodium salt. Preferably, the brightener is present in an amount of 1 ppb to 500 ppm, preferably 50 ppb to 10 ppm.
[0038] Conventional levelers can be used in copper electroplating baths. The levelers included in the acid copper electroplating baths for filling through-holes are preferably reaction products of heterocyclic aromatic compounds and epoxy compounds. An example of a preferred copolymer of aromatic compounds and epoxy compounds used as a leveler is 4-phenylimidazole / imidazole / 1,4-butanediol diglycidyl ether copolymer. The synthesis of such compounds is disclosed in documents such as (Patent Document 1).
[0039] Other additives that may be included in the acid copper electroplating bath are often one or more conventional compounds that are included in acid copper electroplating baths and compositions. Such conventional compounds include, but are not limited to, one or more complexing agents, one or more chloride ion sources, stabilizers for adjusting mechanical properties, providing rate control, refining grain structure and modifying deposition stress, buffers, suppressors and carriers. They may be included in the acid copper electroplating bath in conventional amounts well known to those skilled in the art.
[0040] The method of the present invention can reduce the number and size of voids and eliminate voids from the through-holes, as well as reduce the total surface copper required to fill the through-holes.
[0041] The following examples are included to further illustrate the invention, but are not intended to limit its scope. EXAMPLES
[0042] Examples 1 to 4 of the present invention and Comparative Examples 5 to 7 FR4 / glass-epoxy coupons with a width of 5 cm and a length of 15 cm with multiple through-holes were provided by Cirexx. The through-hole pitch of each coupon was 1000 μm. First, an electroless copper layer was formed on both sides of the coupon and on the walls of the through-holes using CIRCUPOSIT™ 253 electroless process plating formulation and method (available from DuPont Electronics & Industrial, Marlborough, MA). The electroless copper layer thickness on the coupon was about 0.3 μm. The coupons were pre-cleaned with copper cleaners LP200 and EVP-209 available from DuPont Electronics & Industrial, Inc. The coupons were then placed in a 32 L plating tank containing an aqueous copper electroplating bath with a pH of less than 1 and the formulation shown in Table 1.
[0043] [Table 1]
[0044] The coupons were connected to DRPP (Dutch reverse pulse plating) rectifiers. One side (side A) of each coupon was connected to one rectifier and the second side (side B) of each coupon was connected to a second rectifier allowing independent control of current application to each side of the coupon. Each 32 L plating tank contained two DeNora DT-4 iridium coated titanium insoluble anode counter electrodes. Each electrode was connected to one of the two rectifiers to provide voltage to the electrodes. The plating bath was stirred during electroplating at 16 L / min using an educator. Electroplating was performed at room temperature. Copper delamination occurred during forward-reverse pulse plating while copper electroplating occurred on the coupons and on the walls of the through-holes during DC plating.
[0045] Through-hole analysis and copper thickness were measured by X-ray analysis using a Nordson Dage QUADRA™ 5 2D X-ray inspection system. Partial copper bridge measurements were based on the following formula: 0<(X+Y) / 2 / D / 2<1 (II) where the parameters X, Y and D are as defined above.
[0046] Example 1 (present invention) FR4 / glass-epoxy coupons with multiple through-holes, 250 μm thick and 100 μm in diameter, were copper plated to form partial bridges in the through-holes and then fill the complete through-holes. AR=2.5. FIG. 1A shows the first step of the plating method of the present invention. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to simultaneously polarize both sides of each coupon. The DC current was set to 1.5 ASD. After applying DC current to the A side and the B side of each coupon for about 13 seconds and about 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 2. The dashed rectangle in FIG. 1A shows an example of a forward-reverse pulse plating sequence.
[0047] [Table 2]
[0048] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed from DC plating to forward-reverse pulse plating for about 1 second having the same parameters as in Table 2 above. The phase shift offset of the forward-reverse pulse plating from side A to side B was 180°.
[0049] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A-side and B-side of the coupon was repeated until a copper layer of about 3 μm was deposited on the A-side and B-side surfaces of one half of the coupon, while a copper layer of about 9 μm was deposited on the other half of the coupon.
[0050] X-ray analysis was used to measure partial copper bridges as well as any voids in the through-holes. All through-holes showed partial bridge formation. The coupon with a 3 μm copper surface layer had D / 2=50 μm and (X+Y) / 2=14 μm. Ratio=0.28. The coupon with a 9 μm copper surface layer had D / 2=50 μm and (X+Y) / 2=40 μm. Ratio=0.80. No voids were detected in the through-holes. The through-holes were open on both ends and the two side walls were plated with copper. The partial copper bridge formed substantially in the center of the through-hole with a gap or opening between each half of the partial bridge.
[0051] Electroplating to completely fill the through holes of the coupons was performed by reverse pulse plating. Figure IB shows the pulse plating waveform. Table 3 below discloses the plating parameters.
[0052] [Table 3]
[0053] The pulse plating reversal cycle was repeated until the surface copper thickness on all coupons reached approximately 40 μm. The through-holes were inspected for voids by X-ray analysis. All through-holes appeared to be filled and no voids were observed.
[0054] Example 2 (present invention) FR4 / glass-epoxy coupons with multiple through-holes, 250 μm thick and 150 μm in diameter, were copper plated to form partial bridges in the through-holes and then fill the complete through-holes. The AR was 1.7. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to polarize both sides of each coupon simultaneously. The DC current was set to 1.5 ASD. After applying DC current to the A side of each coupon for approximately 13 seconds and to the B side for approximately 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 2 of Example 1.
[0055] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed from DC plating to forward-reverse pulse plating for about 1 second with the same parameters as in Table 2 of Example 1 above. The phase shift offset of the forward-reverse pulse plating from side A to side B was 180°.
[0056] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A-side and B-side of the coupon was repeated until a copper layer of about 7 μm was deposited on the A-side and B-side surfaces of one half of the coupon, while a copper layer of about 9 μm was deposited on the other half of the coupon.
[0057] X-ray analysis was used to measure partial copper bridges as well as any voids in the through-holes. All through-holes showed partial bridge formation. The coupon with a 7 μm copper surface layer had D / 2=75 μm and (X+Y) / 2=36 μm. Ratio=0.48. The coupon with a 9 μm copper surface layer had D / 2=75 μm and (X+Y) / 2=60 μm. Ratio=0.80. No voids were detected in the through-holes. The through-holes were open on both ends and the two side walls were plated with copper. The partial copper bridge formed substantially in the center of the through-hole with a gap or opening between each half of the partial bridge.
[0058] Electroplating to completely fill the through-holes of the coupons was performed by reverse pulse plating. Table 3 in Example 1 above discloses the plating parameters. The pulse plating reverse cycle was repeated until the surface copper thickness on all coupons reached approximately 40 μm. The through-holes were inspected for voids by X-ray analysis. All through-holes appeared to be filled and no voids were observed.
[0059] Example 3 (present invention) FR4 / glass-epoxy coupons with multiple through-holes, 400 μm thick and 200 μm in diameter, were copper plated to form partial bridges in the through-holes and then fill the complete through-holes. AR=2. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to polarize both sides of each coupon simultaneously. The DC current was set to 1.5 ASD. After applying DC current to the A side of each coupon for approximately 13 seconds and to the B side for approximately 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 2 of Example 1.
[0060] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed from DC plating to forward-reverse pulse plating for about 1 second with the same parameters as in Table 2 of Example 1 above. The phase shift offset of the forward-reverse pulse plating from side A to side B was 180°.
[0061] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A-side and B-side of the coupon was repeated until a copper layer of about 10 μm was deposited on the A-side and B-side surfaces of one half of the coupon, while a copper layer of about 13 μm was deposited on the other half of the coupon.
[0062] X-ray analysis was used to measure partial copper bridges as well as any voids in the through-holes. All through-holes showed partial bridge formation. The coupon with a 3 μm copper surface layer had D / 2=100 μm and (X+Y) / 2=48 μm. Ratio=0.48. The coupon with a 13 μm copper surface layer had D / 2=200 μm and (X+Y) / 2=70 μm. Ratio=0.70. No voids were detected in the through-holes. The through-holes were open on both ends and the two side walls were plated with copper. The partial copper bridge formed substantially in the center of the through-hole with a gap or opening between each half of the partial bridge.
[0063] Electroplating to completely fill the through-holes of the coupons was performed by reverse pulse plating. Table 3 in Example 1 above discloses the plating parameters. The pulse plating reverse cycle was repeated until the surface copper thickness on all coupons reached approximately 40 μm. The through-holes were inspected for voids by X-ray analysis. All through-holes appeared to be filled and no voids were observed.
[0064] Example 4 (present invention) FR4 / glass-epoxy coupons with multiple through-holes, 800 μm thick and 250 μm in diameter, were copper plated to form partial bridges in the through-holes and then completely fill the through-holes. The AR was 3.2. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to polarize both sides of each coupon simultaneously. The DC current was set to 1.5 ASD. After applying DC current to the A side of each coupon for approximately 13 seconds and to the B side for approximately 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 2 of Example 1.
[0065] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed from DC plating to forward-reverse pulse plating for about 1 second with the same parameters as in Table 2 of Example 1 above. The phase shift offset of the forward-reverse pulse plating from side A to side B was 180°.
[0066] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A-side and B-side of the coupon was repeated until a copper layer of about 10 μm was deposited on the A-side and B-side surfaces of one half of the coupon, while a copper layer of about 14 μm was deposited on the other half of the coupon.
[0067] X-ray analysis was used to measure partial copper bridges as well as any voids in the through-holes. All through-holes showed partial bridge formation. The coupon with a 10 μm copper surface layer had D / 2=125 μm and (X+Y) / 2=87 μm. Ratio=0.70. The coupon with a 14 μm copper surface layer had D / 2=125 μm and (X+Y) / 2=107 μm. Ratio=0.86. No voids were detected in the through-holes. The through-holes were open on both ends and the two side walls were plated with copper. The partial copper bridge formed substantially in the center of the through-hole with a gap or opening between each half of the partial bridge.
[0068] Electroplating to completely fill the through-holes of the coupons was performed by reverse pulse plating. Table 3 in Example 1 above discloses the plating parameters. The pulse plating reverse cycle was repeated until the surface copper thickness on all coupons reached approximately 40 μm. The through-holes were inspected for voids by X-ray analysis. All through-holes appeared to be filled and no voids were observed.
[0069] Example 5 (Comparative Example) FR4 / glass-epoxy coupons with a thickness of 250 μm and a number of 100 μm diameter through-holes were copper plated to form a complete bridge in the through-holes and then fill the complete through-holes. AR=2.5. FIG. 1A shows the first step of the plating method of the present invention. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to polarize both sides of each coupon simultaneously. The DC current was set to 1.5 ASD. After applying DC current to the A side and the B side of each coupon for about 13 seconds and about 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 4.
[0070] [Table 4]
[0071] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed from DC plating to forward-reverse pulse plating for about 1 second having the same parameters as in Table 4 above. The phase shift offset of the forward-reverse pulse plating from side A to side B was 180°.
[0072] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A and B sides of the coupon was repeated until a copper layer of approximately 11 μm was deposited on the A and B side surfaces of the coupon halves.
[0073] The coupons were analyzed by X-ray analysis to determine if a complete bridge had formed in the through-holes. All through-holes showed complete bridging. Figure 4 shows a cross-section of a through-hole with a complete copper bridge. The through-hole was open on both ends forming two vias, and the two side walls were plated with copper. The copper bridge was formed substantially in the center of the through-hole. The bridge ratio was 1. No voids were detected in the through-holes.
[0074] Electrolytic plating to completely fill the through-holes was performed by DC plating. Figure 5 shows the DC waveform. DC plating was performed for 100 seconds at a current density of 1.5 ASD to deposit a final copper thickness of approximately 40 μm on both sides A and B of the board. The coupons were inspected for copper fill of the through-holes and for voids. Although the through-holes were filled with copper, substantial voids were observed within the through-holes.
[0075] Example 6 (Comparative Example) FR4 / glass-epoxy coupons with multiple through-holes, 250 μm thick and 150 μm in diameter, were copper plated to form a complete bridge in the through-holes and then fill the complete through-holes. The AR was 1.7. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to polarize both sides of each coupon simultaneously. The DC current was set to 1.5 ASD. After applying DC current to the A side of each coupon for approximately 13 seconds and to the B side for approximately 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 4 of Example 5.
[0076] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed to forward-reverse pulse plating for about 1 second. The phase shift offset of the forward-reverse pulse plating of side A relative to side B was 180°.
[0077] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A and B sides of the coupon was repeated until a copper layer of approximately 10 μm was deposited on the A and B side surfaces of the coupon halves.
[0078] X-ray analysis was used to determine the bridging of the through-holes. All through-holes showed complete bridging. The bridge ratio was 1. No voids were detected in the through-holes.
[0079] Electroplating to completely fill the through-holes was performed by DC plating. DC plating was performed for 100 seconds at a current density of 1.5 ASD to deposit a final copper thickness of approximately 40 μm on both sides A and B of the board. The coupons were inspected for copper fill of the through-holes and for voids. Although the through-holes were filled with copper, substantial voids were observed within the through-holes.
[0080] Example 7 (Comparative Example) FR4 / glass-epoxy coupons with multiple through-holes, 400 μm thick and 200 μm in diameter, were copper plated to form a complete bridge in the through-holes and then filled with the complete through-holes. AR=2. A voltage generated by a rectifier was applied to allow DC current across the A and B sides of each coupon to polarize both sides of each coupon simultaneously. The DC current was set to 1.5 ASD. After applying DC current to the A side of each coupon for approximately 13 seconds and to the B side for approximately 6 seconds, the rectifier for the B side was switched from DC plating to a forward-reverse pulse plating sequence with parameters disclosed in Table 4 of Example 5 above.
[0081] After a period of about 1 second, the forward-reverse pulse plating sequence on side B was changed back to DC plating. After about 13 seconds, the DC plating on side A was changed to forward-reverse pulse plating for about 1 second. The phase shift offset of the forward-reverse pulse plating of side A relative to side B was 180°.
[0082] The aforementioned electroplating cycle of DC current followed by forward-reverse pulse plating with a phase offset of 180° on the A and B sides of the coupon was repeated until a copper layer of approximately 15 μm was deposited on the A and B side surfaces of the coupon halves.
[0083] X-ray analysis was used to determine the bridging of the through-holes. All through-holes showed complete bridging. The bridge ratio was 1. No voids were observed.
[0084] Electroplating to completely fill the through holes was performed by DC plating. DC plating was performed for 100 seconds at a current density of 1.5 ASD to deposit a final copper thickness of approximately 40 μm on both sides A and B of the board. The coupons were inspected for copper fill of the through holes and for voids. The through holes were filled with copper. Some voids were observed. [Explanation of symbols]
[0085] 10 Through Hole 12 Substrate 14 Copper 16. Wall 18 Copper 20 Partial Bridge 22 Gap 24A opening 24B opening 30 through hole 32 Substrate 34 Copper layer 36 Partial copper bridge 38 Gap 40 Open end 50 through hole 52 Substrate 54 Copper layer 56 Full copper bridge 58 Via 60 Via
Claims
1. a) providing a substrate including a first side and a second side having a plurality of through holes; b) immersing the substrate in a copper plating bath; c) simultaneously polarizing the first side of the substrate with a rectifier and polarizing the second side of the substrate with the rectifier to generate currents on the first side and the second side of the substrate; d) plating partial copper bridges in the plurality of through holes by simultaneously applying a plating cycle to the first and second sides of the substrate, the plating cycle including applying a DC current on the first and second sides of the substrate, followed by applying a first pulse train on the first side of the substrate and a second pulse train on the second side of the substrate, the first pulse train and the second pulse train being offset by 180° of the plating cycle; and then: e) filling the through holes with copper by applying a pulsed plating reverse current to the substrate; Including, The method wherein the through-holes have an aspect ratio of thickness:diameter of 1.6:1 to 5:
1.
2. 2. The method of claim 1, wherein a DC current density on the first side and the second side of the substrate ranges from 0.5 ASD to 10 ASD.
3. 2. The method of claim 1, wherein the pulse train on the first side and the pulse train on the second side of the substrate have a forward current density of 0.5 ASD to 10 ASD and a reverse current density of -1.5 ASD to -30 ASD.
4. 2. The method of claim 1, wherein the pulse plating reverse current has a forward current density of 0.5 ASD to 10 ASD and a reverse current density of -0.15 ASD to -2.5 ASD.
5. The method of claim 1 , wherein the substrate has a thickness of 150 to 800 μm.
6. The method of claim 1 , wherein the plurality of through holes has an average diameter of 100 to 300 μm.
7. The method of claim 1 , wherein the partial bridge has a partial bridge ratio greater than zero but less than one.
8. The method of claim 1, wherein the through hole has an aspect ratio of thickness:diameter of 1.6:1 to 2:1.
Citation Information
Patent Citations
Electrical treatment for filling through-holes with metal, particularly electrical treatment for filling through-holes with copper in printed circuit boards.
JP2008513985A
Method of manufacturing printed wiring board
JP2015106653A
Method for manufacturing printed wiring board
US20150156888A1
Plating bath and method
US8268158B2
Single step electrolytic method of filling through holes in printed circuit boards and other substrates
WO2021091743A1